THE EFFECT OF USING STILL PICTURES ON STUDENTS’ ACHIEVEMENT IN WRITING PROCEDURE TEXT - Siti Hajar; Sumarsih (Universitas Negeri Medan, 2014)
This study aims to find out whether students’ achievement through using still Pictures is higher than through motion pictures in writing procedure text. The research was conducted by experimental research used in two groups. They are experimental use still pictures and control use motion pictures. The subject of this study were the students of SMA Swasta Abdi Negara class XI2 and XI3 consisted of 30 students for each classes. To collecting the data was taken from writing test. Based on the calculation, it shows that the reliability of the test was 0,81 categorized as very high reliability.After analyzing the data,it was found that the value of to was 3.644 with the degree of freedom (df)=58 at the level of significance p(0,05)=2,004.It means that to is higher than tt. It was found that teaching procedure text by use still pictures is higher than use motion pictures. Still pictures has a significant effect on students’ achievement in writing procedure text.